Clinical and radiobiological comparison of two palliative regimens of radiotherapy in advanced squamous cell carcinoma of head and neck: a prospective randomized study (Bangladesh Journal of Otorhinolaryngology, 2011)
Objective: The aim of this study is to compare two different palliative radiotherapy regimes - standard hypofractionated regime and split course hypofractionated regime in advanced head and neck cancer.  Methods: 60 untreated patients of advanced squamous cell carcinoma of head and neck who were treated with palliative intent were randomized into two arms: Arm A (n=30) patients received 30 Gy in 10 fractions in two weeks; Arm B (n=30) patients received 1750 cGy in 5 fractions followed by a three weeks gap and then again 1750 cGy in 5 fractons, treatment completed in 5 weeks. Result: The response was comparable in both the arms. Symptom palliation was also similar; pain relief was 76% in both arms and relief of dysphagia 73% in arm A vs 79% in arm B. Partial response rate was equivalent (69% vs 62%). Mucositis and upper GI toxicity did not show any significant difference. Patient drop out was only 1 in arm B compared to 4 in arm A. The BED10 values are 39 and 37.84 in arm A and B respectively; whereas the BED3 values are 60 and 75.8. Conclusion: We conclude that the second regime can also be used in palliative setting in some selected patients. Key words: Advanced head and neck cancer; Palliative Radiation. DOI: 10.3329/bjo.v17i1.7620 Bangladesh J Otorhinolaryngol 2011; 17(1): 29-35